Counselling appointment booking through telegram bot for UiTM Jasin / Sharifah Amirah Zulaikha Syed Ahmad Kamal - Syed Ahmad Kamal, Sharifah Amirah Zulaikha (Faculty of Computer and Mathematical Sciences, 2018)
In the past years, we have seen an explosion of booking applications using smartphone across multiple industries. Most of people nowadays communicated using social messenger but still downloaded booking applications to book many reservations such as hotels, flights and others. Fortunately, people can book with bots through Telegram and saves time to search a certain booking bots on the Play Store. Bots are third-party applications that run inside Telegram and users can interact with bots by sending it messages, commands and inline requests. In Universiti Teknologi Mara (UiTM) Melaka, Jasin Campus, before booking an appointment with one of the counselors, the visitor needs to see or call the desired counselor to set an appointment which most of the visitors do not have time to do so. Therefore, this project propose a counseling session appointment booking bot for UiTM Jasin, to saves time and allow user to book an appointment and update the counselor through notification. In order to complete this project, a booking system with availability checking are connected through bot to send notification of the booking made to the counselor and a reminder to notify user. Based on the Functionality Test and User Acceptance Test, this booking bot has fulfilled all the requirements to efficiently book a counseling session without seeing or calling the counselors. In conclusion, by using the counseling booking appointment bot, the booked session has increased and the bot has eased the counselors of UiTM Jasin to update their schedule.